2019
DOI: 10.1213/ane.0000000000004275
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Factor Levels and Underlying Thrombin Generation Patterns in Adult Extracorporeal Membrane Oxygenation Patients

Abstract: BACKGROUND: There is a paucity of data on the underlying procoagulant–anticoagulant balance during extracorporeal membrane oxygenation (ECMO). We hypothesized that adult ECMO patients would have an imbalance between procoagulant and anticoagulant factors, leading to an abnormal underlying thrombin generation (TG) pattern. METHODS: Twenty adult venoarterial (VA) ECMO patients had procoagulant and anticoagulant factor levels measured temporally on ECMO da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 22 publications
2
48
0
Order By: Relevance
“…Resistance to thrombo modulin is also apparent. These changes demonstrate a possible mechanism for hypercoagulability during adult VA ECMO [41].…”
Section: Complications Of Extra Corporeal Therapy Bleeding and Anticmentioning
confidence: 77%
See 1 more Smart Citation
“…Resistance to thrombo modulin is also apparent. These changes demonstrate a possible mechanism for hypercoagulability during adult VA ECMO [41].…”
Section: Complications Of Extra Corporeal Therapy Bleeding and Anticmentioning
confidence: 77%
“…Mazzeffi et al [41] observed that contact activation occurs during ECMO, but procoagulant factor levels are generally preserved. Although heparin-neutralized thrombin generation (TG) is delayed, peak TG and endogenous thrombin potential are supranormal in the setting of high FVIII and low AT and protein C levels.…”
Section: Complications Of Extra Corporeal Therapy Bleeding and Anticmentioning
confidence: 99%
“…1,[14][15][16] Furthermore, pathophysiological mechanisms of ECMO-induced coagulopathy is multifactorial and involves both humoral and cellular coagulation elements as well as inflammatory system. [17][18][19] Acquired AT deficiency is not uncommon due to prolonged heparin usage on ECMO, and AT may reduce the risk of in vivo or intracircuit thrombus formation. 18,20,21 Accordingly, since children have AT deficiency at least until they are 6 months/1 year old, AT has been administered during ECMO in critically ill children in case of disseminated intravascular coagulation due to sepsis and liver impairment.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Acquired AT deficiency is not uncommon due to prolonged heparin usage on ECMO, and AT may reduce the risk of in vivo or intracircuit thrombus formation. 18,20,21 Accordingly, since children have AT deficiency at least until they are 6 months/1 year old, AT has been administered during ECMO in critically ill children in case of disseminated intravascular coagulation due to sepsis and liver impairment. [22][23][24][25][26] Over the last decade, several reports and case series have suggested a potential usefulness of AT replacement in adults during veno-venous (V-V) ECMO, demonstrating lower heparin requirement, better control of anticoagulation, or lower consumptions of coagulation factors and platelets.…”
Section: Introductionmentioning
confidence: 99%
“…Reflective of the regulatory nature of these cascades is the presence of modestly elevated D-dimer levels in adult ECMO patients. 15 Intriguingly, the COVID-19 literature has within it numerous reports of elevated D-dimers, which represents the most frequently assayed fibrin degradation products (FDP), and are generated during enzymatic fibrin cleavage by plasmin. 1 , 16 D-dimer levels in COVID-19 patients serve as biomarkers, with elevated levels being associated with increased disease severity and higher in hospital mortality.…”
mentioning
confidence: 99%